PERAN PENYULUH PERTANIAN TERHADAP KETERAMPILAN PETANI PADI DI KELOMPOK TANI SIDOMAKMUR I DI DESA DENGKEK KECAMATAN PATI KABUPATEN PATI - Wardhani, Wardhani (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
This study aims to determine the role of extension agents to improve farmers skills. The study was conducted in December 2017 in Sidomakmur I farmer group Pati District Pati Regency. The method used in the study was survey. Sample was taken by purposive sampling method with the number of respondents as many as 50 farmers. Data were analysed by multiple linear regression. The result simultaneously and separately the role of extension agents as facilitator, motivator, educator and communicator had significant effect on farmers skills.